MECHANISATION AND AUTOMATION IN CONTACT WELDING - Turdiyev Abdurasul Khalilovich; Abdullayev Jura Khudoyorovich (Web of Journals Publishing, 2024)
The main task of control devices in contact welding is to implement the given program in a certain time by transmitting control signals in analog or discrete form to the functional nodes of the control devices.
Keywords: Contact welding, analog or discrete, passive and active control, welding equipment, mode cycle and parameter control unit.